1975
DOI: 10.2118/4653-pa
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Perforated Completions in Formations With or Without Damage

Abstract: The productivity of perforated completions situated in either homogeneous reservoirs or zones of permeability damage is described. Calculations for both types of reservoirs require use of a perforation skin factor; calculations for a damaged reservoir additionally require a damage skin factor. Nomograms are presented for calculating these factors. Introduction In perforated completions, fluids enter the wellbore through tunnels made by bullets or jets that pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…A great number of experimental, numerical, empirical, and semianalytical models have been constructed to predict the perforation pseudoskin and perforation total skin (Jones and Slusser 1974;Harris 1966;Klotz et al 1974;Hong 1975;Locke 1981;Tariq 1987;McLeod 1983;Karakas 1991;Bell et al 1995;SPAN 1999;SPAN 2002;Thomas et al 1992;Yildiz 2002;Pan and Tang 1989). Some of these models will be described briefly below.…”
Section: Perforation Total Skin Factormentioning
confidence: 99%
“…A great number of experimental, numerical, empirical, and semianalytical models have been constructed to predict the perforation pseudoskin and perforation total skin (Jones and Slusser 1974;Harris 1966;Klotz et al 1974;Hong 1975;Locke 1981;Tariq 1987;McLeod 1983;Karakas 1991;Bell et al 1995;SPAN 1999;SPAN 2002;Thomas et al 1992;Yildiz 2002;Pan and Tang 1989). Some of these models will be described briefly below.…”
Section: Perforation Total Skin Factormentioning
confidence: 99%
“…In his analysis perforations were represented by mathematical sinks distributed spirally around the wellbore and did not extend into the formation. Other early investigators used finite difference modelling approaches to examine the flow in perforated completions (e.g., Harris, 1966;Hong, 1975;Bell et al, 1972). Klotz et al (1974), Locke (1981) and Tariq (1987) were the first to apply the finite element method, which models the geometry of the perforation with greater precision.…”
Section: Introductionmentioning
confidence: 99%
“…He also conducted a grid-or mesh-sensitivity analysis to ascertain the effect of grid or mesh size on their results without the non-Darcy effect. Based on this exercise, Tariq concluded that Harris (1966) and Hong (1975) used insufficient grid cells and unrealistic wedge-shaped perforations in their study, and although Locke's geometrical representation (1987) was precise, the grid size 0920-4105/$ -see front matter D 2005 Elsevier B.V. All rights reserved. doi:10.1016/j.petrol.2005.10.004 was too large for accurate modelling of high pressure gradients near the perforation tip.…”
Section: Introductionmentioning
confidence: 99%
“…Muskat (1943) presented the first analytical treatment of the problem in 1943 representing perforation tunnels as point sinks in his analysis. Other early investigators used finite difference modelling approaches to examine the flow in perforated completions (e.g., Harris, 1966;Hong, 1975;Bell et al, 1972). Later investigators applied finite element methods, which model the geometry of the perforation with greater precision (e.g., Koltz et al, 1974;Locke 1981;Tariq, 1987).…”
Section: Introductionmentioning
confidence: 99%